Beneficial actions of a long‐acting apelin analogue in diabetes are related to positive effects on islet cell turnover and transdifferentiation. Issue 12 (21st September 2020) - Tanday, Neil; Irwin, Nigel; Moffett, R. Charlotte; Flatt, Peter R.; O'Harte, Finbarr P. M.
Abstract: Aim: The current study has tested the hypothesis that the positive effects of apelin receptor activation in diabetes are linked to benefits on islet cell apoptosis, proliferation and transdifferentiation using Ins1 Cre/+ ; Rosa26‐eYFP transgenic mice and induction of diabetes‐like syndromes by streptozotocin (STZ) or high‐fat feeding. Materials and methods: Groups (n = 6–8) of streptozotocin (STZ)‐induced diabetic and high‐fat diet (HFD)‐fed mice received once‐daily injection (25 nmol/kg) of the long‐acting acylated apelin‐13 analogue, pGlu(Lys 8 Glu‐PAL)apelin‐13 amide, for 10 or 12 days, respectively. Results: pGlu(Lys 8 Glu‐PAL)apelin‐13 amide treatment partly reversed body weight loss induced by STZ and normalized circulating insulin. There was no effect of pGlu(Lys 8 Glu‐PAL)apelin‐13 amide on these variables in HFD‐fed mice, but an increase in pancreatic insulin content was observed. pGlu(Lys 8 Glu‐PAL)apelin‐13 amide also fully, or partially, reversed the detrimental effects of STZ and HFD on plasma and pancreatic glucagon concentrations. In HFD‐fed mice, the apelin analogue decreased dietary‐induced elevations of islet, β‐ and α‐cell areas, whilst reducing α‐cell area in STZ‐induced diabetic mice. In terms of islet cell lineage, pGlu(Lys 8 Glu‐PAL)apelin‐13 amide effectively reduced β‐ to α‐cell transdifferentiation and helped maintain β‐cell identity, which was linked to elevated Pdx‐1 expression. These islet effects were coupled with decreased β‐cell apoptosis and α‐cell proliferation in both models, and there was an accompanying increase of β‐cell proliferation in STZ‐induced diabetic mice. Conclusion: Taken together these data demonstrate, for the first time, that pancreatic islet benefits of sustained APJ receptor activation in diabetes are linked to favourable islet cell transition events, leading to maintenance of β‐cell mass.